Depletion of Gut Microbiota Impairs Gut Barrier Function and Antiviral Immune Defense in the Liver - Guo, Weina; Zhou, Xin; Li, Xiaoran; Zhu, Qingfeng; Peng, Jing; Zhu, Bin; Zheng, Xin; Lu, Yinping; Yang, Dongliang; Wang, Baoju; Wang, Junzhong (Frontiers in Immunology, 2021)
Commensal gut microbiota protects the immune defense of extra-intestinal organs. Gut microbiota depletion by antibiotics can impair host antiviral immune responses and alter hepatitis B virus (HBV) infection outcomes. However, how gut microbiota modulates antiviral immune response in the liver remains unclear. Here, mice were treated with broad-spectrum antibiotics to deplete gut microbiota. Gut integrity was evaluated, and translocation of live commensal gut bacteria and their components into the liver was investigated. An HBV infection model was established to evaluate impairment of antiviral immune response in the liver after gut microbiota depletion. We found that gut microbiota depletion was associated with impairment of colon epithelial integrity, and live commensal gut microbiota could translocate to the liver. Further, T cell antiviral function in the liver was impaired, partially relying on enhanced PD-1 expression, and HBV immune clearance was hampered. In conclusion, gut microbiota depletion by antibiotics can impair gut barrier function and suppress T cell antiviral immune response in the liver.